Architectural modelmaking - Dunn, Nick (London : Laurence King Publishing, 2014)
The physical model is an important communication tool for architects. Although the proliferation of CAD programs has enabled the creation of increasingly complex computer models and virtual environments, there is also a growing need to address the three-dimensional qualities of architecture that may be lost when using such media. This book focuses on the inspiring possibilities for modeling the built environment with all the different media and techniques available. In describing the use of different models in different contexts, the book provides a practical guide to how and why models are used and what they are used for. This second edition includes more detailed step-by-step exercises, expanded discussion of materials and techniques, and updated coverage of digital techniques.
Previous edition: 2010.
Formerly CIP.
boek